The Congruent Facelift A Three-dimensional View - Ho, Lawrence C. Y. (Springer International Publishing, 2018)
This book deals with a special form of facial rejuvenative surgery, which considers the three-dimensional anatomy of the face and benchmarks it against biomechanical models of the face. Traditional approaches to the ageing human face have been based on a two-dimensional approach. The authors, however, consider the human face using a three-dimensional platform that reflects height, width and depth and thus defines spatial divisions or pilasters. The anatomically accurate and bio-physically based three-dimensional computational models, originally used to simulate facial expressions and subsequently in the dynamic evaluation of the various soft tissues, offer a valuable new tool for surgical techniques. The book is divided into four chapters, the first of which describes the historical developments, evolution of facelift procedures and review of traditional two-dimensional approach. The second chapter presents three-dimensional surgical anatomy of the face and neck with the introduction of "facial pilasters". Treating the human face as a collection of compliant and rigid structural components which obey engineering principles and its biomechanical behaviour is discussed in chapter three. The last chapter provides the reader comprehensive information on the surgical procedure for contour vector congruent facelift, including case studies. An alternative approach (Rejuvenative Facial Lipomorphoplasty) to the de-volumed ageing face with little sagging and skin excess is introduced together with case studies. This book was motivated by the desire to define the key steps in facelift techniques and provides an essential guide for young plastic surgeons, as well as experienced surgeons who are dissatisfied with the current two-dimensional platform.